The Heat Shock Protein 40-Type Chaperone MASH Supports the Endoplasmic Reticulum-Associated Degradation E3 Ubiquitin Ligase MAKIBISHI1 in Medicago truncatula - Erffelinck, Marie-Laure; Ribeiro, Bianca; Gryffroy, Lore; Rai, Avanish; Pollier, Jacob; Goossens, Alain (Frontiers in Plant Science, 2021)
Jasmonates (JA) are oxylipin-derived phytohormones that trigger the production of specialized metabolites that often serve in defense against biotic stresses. In Medicago truncatula, a JA-induced endoplasmic reticulum-associated degradation (ERAD)-type machinery manages the production of bioactive triterpenes and thereby secures correct plant metabolism, growth, and development. This machinery involves the conserved RING membrane-anchor (RMA)-type E3 ubiquitin ligase MAKIBISHI1 (MKB1). Here, we discovered two additional members of this protein control apparatus via a yeast-based protein–protein interaction screen and characterized their function. First, a cognate E2 ubiquitin-conjugating enzyme was identified that interacts with MKB1 to deliver activated ubiquitin and to mediate its ubiquitination activity. Second, we identified a heat shock protein 40 (HSP40) that interacts with MKB1 to support its activity and was therefore designated MKB1-supporting HSP40 (MASH). MASH expression was found to be co-regulated with that of MKB1. The presence of MASH is critical for MKB1 and ERAD functioning because the dramatic morphological, transcriptional, and metabolic phenotype of MKB1 knock-down M. truncatula hairy roots was phenocopied by silencing of MASH. Interaction was also observed between the Arabidopsis thaliana (Arabidopsis) homologs of MASH and MKB1, suggesting that MASH represents an essential and plant-specific component of this vital and conserved eukaryotic protein quality control machinery.